A smart "shear sensing" bolt based on FBG sensors. (July 2018) - Ren, Liang; Feng, Tangzheng; Ho, Michael; Jiang, Tao; Song, Gangbing
Abstract: This paper develops a new type of smart bolt that can simultaneously measure the axial and shear forces through the use of embedded fiber Bragg gratings (FBG) sensors. Based on the linear relationship between the equivalent bending moment and the shear force, the equation to calculate the shear force using the Bragg wavelength variation is derived. A method to design a smart bolt is presented in this paper. To enable the experimental study, a smart bolt was fabricated, calibrated, and tested. Calibration of the smart bolt reveals a linear relationship between the reflected Bragg wavelength and the applied shear forces and axial forces. The variation of the wavelengths of the embedding FBGs in different positions in the bolt was analyzed, and a model was developed to relate the FBG wavelength to axial and shear forces experienced by the bolt. Experimental results demonstrate that this smart bolt is suitable for bolt axial forces monitoring and shear forces monitoring.